PUBLIC ADMINISTRATION IN DEVELOPMENT OF THE PROCEDURE OF THE SECURING A CLAIM - Gvozdevičs, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The Ministry of Justice of the Republic of Latvia is a leading public administration in the justice sectors and plays an important role in the development of the procedure of the securing a claim. Topicality and novelty of the research are reflected in the fact that until now in the legal doctrine weren’t made depth and extensive researches of the role of public administration in solving problems of the securing a claim. The aim of the research is to carry out an assessment of the activities of the Ministry of Justice in the development of the securing a claim. In the present research, using the analytical, descriptive and deduction/induction method, were analysed the normative acts, legal policy planning documents, annotations of draft amendments to the Civil Procedure Law, etc. Results: actions of the Ministry of Justice to develop the securing a claim sometimes are chaotic. Conclusions: in order to achieve the defined objectives of the institute of the securing a claim, the state should pay attention to the systematic improvement of current civil procedural regulation.